DEVELOPMENT OF A BLENDED LEARNING MODEL BY USING AN ACTIVE LEARNING METHOD TO ENHANCE PRE-SERVICE TEACHER EDUCATION STUDENTS’ INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) COMPETENCIES - DITSIRI, TOSSAPORN; RAMPAI, NATTAPHON; SIRIPIPATTANAKUL, SUTITHEP (Research Community and Social Development Journal, 2021)
The two purposes of this research were: 1) to analyze and synthesize a blended learning model by using an active learning method designed to enhance pre-service teacher education students’ ICT competencies; and 2) to develop a blended learning model by using an active learning method to enhance pre-service teacher education students’ ICT competencies. The study’s procedure was divided into 2 steps: 1) synthesizing the models through the technique of document synthesis. The sample selected by purposive sampling was experts in education, totaling 5 people. An interview guide was used to collect data which then were synthesized for the development of the instructional model; and 2) assessing the appropriateness of the instructional model. The sample was 5 experts for assessing the appropriateness of the instructional model. A 5-point rating scale questionnaire was used to collect data. Data analysis was conducted using mean and standard deviation. The three main findings of the research were as follows: The model was composed of 4 elements: 1) instructor, 2) learner, 3) classroom, 4) technology and the model of blended learning by using an active learning method was appropriately suitable at the highest level ( =4.91, S.D.=0.15); and 3) the model of blended learning by using an active learning method achieved a quality at the highest level ( =4.92, S.D.=0.11).